A Problem of Middlebrow Style: Dialect and Translation in Elena Ferrante’s Naples Tetralogy - Richard Robinson (Textual Practice, 2022)
In what ways does the Bakhtinian model of novelistic discourse, in which dialects are conceived as styles and styles as dialects, apply in the age of world literature and world English? If the style of the contemporary world-novel is purposely drained of its heteroglossia, it risks complicity with a frictionless communicability. This essay argues that the near-complete absence of napoletano in Elena Ferrante’s Neapolitan novels, despite its magmatically latent energy, emphasises a refusal both to utter and be uttered by dialectal delinquency. The narrator says after Bakhtin ‘“I am me” in someone else’s language, and in [her] own language, “I am other”’, but without any relish in dialogism. Canonical writers such as Verga, Svevo, Pasolini and Ginzburg also respond to the extraordinary rapidity with which dialects were largely subsumed by spoken as well as written Italian. Yet Ferrante prompts new questions about how the global cultures of reception are gendered. She resists the narcissistically masculinist performance of a named style, implicitly and pseudonymously writing for the majority female readership. Ferrante embraces the gendered sensibility of the primarily female ‘middlebrow’, a category now conceived without stigma as immersive, pleasure-giving, cognitively complex and generically transgressive. Under such conditions, the questione linguistica is repeatedly confronted in narrative: its evasion in language marks both the constraints and possibilities of pan-feminist translatability in the ‘world lit’ economy.